Penerapan Advance Organizer Dengan Model Pembelajaran Ekspositori Berpola Lesson Study Untuk Meningkatkan Hasil Belajar Fisika Peserta Didik - Harjono, Ahmad; Gunada, I Wayan; Sutrio, Sutrio; Hikmawati, Hikmawati (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2018)
This study aims to improve the quality of learning through the implementation of lesson study (LS) with expository learning model assisted advance organizer to improve activity and learning outcomes. Implementation of LS is done in SMA Negeri 3 Mataram by taking X class MIA3 and considered appropriate. LS is executed in two action cycles with stages plan, do (implementation and observation), and see (reflection). The research data are qualitative and quantitative data. Qualitative data are derived from important notes of planning and implementation phases and instructional sheet of instructional learning, student activity, and teacher activity, as well as the reflection stage. Quantitative data are analyzed to see improvements in learning outcomes. Implementation of lesson study through expository model assisted by advace organizer can improve physics learning result of class X student of MIA3 SMAN 3 Mataram. The average score of student activity increases from 22.17 with active category in cycle I to 28.85 with very active category in cycle II. Increased classical completeness achievement 70% cycle I to 91% in cycle II.